Temperature Effect on Refractive Index and Density of Pancaguna Taila. - SAXENA, R.B. (Asian Journal of Chemistry, 2010)
In the present communication the relationship between density and refractive index, and the effect of temperature on density and refractive indices of Pancaguna Taila have been discussed.